Emotional relief for patients and nurses in Traditional Chinese Medicine clinics (中医护理门诊工作中缓解患者及护士焦虑情绪的方法) - CHU Yina (初伊娜); TIAN Jing (田婧) (中西医结合护理)
This paper briefly discussed the emotional relief for patients and nurses in Traditional Chinese Medicine clinics, in order to provide reference for nursing quality improvement in Traditional Chinese Medicine clinics.